OPTIMIZING TRADITIONAL MARKET FUNCTIONS FOR CULINARY MSMES IN YOGYAKARTA CITY - Nelly Tiurmida; Utami Sulistiana; Tomi Agus Triono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The research about optimizing the function of the traditional market for Culinary Small and Medium Enterprises in Yogyakarta aims to explore the condition of thirty traditional markets in Yogyakarta and to explore Culinary Small and Medium Enterprises guided by Departments of Industry Cooperative and Yogyakarta Small and Medium Enterprise. This research usedthe exploratory qualitative method. Qualitative research aims to understand the phenomenon that is happening in the traditional market, which is experienced by the research subject such as trader, market headman, market association, and government policy in market management. The exploratorymethod’s purpose is to describe an object deeply and do a search, particularly in concept stabilization that will be used in the wider scope of research with a bigger conceptual reach. The analysis tool is using Strength, Weakness, Opportunity, and Threat (SWOT). The data is collected by using observation, interview, documentation study, and Focus Group Discussion (FGD). The informants are determined through purposive sampling. Data analysis is using the Miles and Huberman model, doneinteractively and continuously to produce saturated data. Explorations result found that 8 traditional markets are recommended in optimizing the function of the traditional market. Eight traditional markets are Ngasem, Kranggan, Karangwaru, Pujokusuman, Legi, Tunjungsari, Gedongkuning, and Gading. However, only three traditional markets which will be tested to sell together, both off-line or online are Kranggan, Ngasem, and Tunjungsari. Afterward, the three traditional markets are given brands suitable with the morning market brand on each traditional market. Kranggan market with brand food court millennial, Ngasem market with a brand food court of Mataram food, and Tunjungsari market with a brand food court of Nusantara food. Keywords: Traditional Market, Culinary Small, and Medium Enterprise.